Drivers of environmental sustainability practices among undergraduate students in UTAR - Lim, Tian He; Tan, Kian Yew (2024)
Environmental sustainability practices are actions taken to reduce the harmful effects of operations on the environment. Recently, sustainability development has faced a lot of obstacles due to many believe that there is a contradiction between environmental sustainability development and economic growth. Therefore, this research project aims to study what factors are affecting UTAR undergraduates' decision in taking actions to protect the environment. In addition, the purpose of conducting this study is to study the influences of social norms, personal norms, environmental awareness, environmental knowledge, and social media on environmental sustainability practices. To perform this study, online questionnaires were distributed to 387 undergraduate students at UTAR Kampar. The sampling method chosen for this study is simple random sampling. After that, Statistical Package for the Social Sciences (SPSS) version 29.0 was used to conduct multiple linear regression analysis. The results of the analysis showed that social norms, personal norms, and environmental knowledge have a significant relationship with environmental sustainability practices. These findings indicate the need for integration of environmental sustainability practices into the curriculum activities by the university and the government. Keywords: Environmental Sustainability Practices, Social Norms, Personal Norms, Environmental Awareness, Environmental Knowledge, Social Media.